Binocular vision problem and amblyopia cases in IIUM Optometry Clinic: a retrospective analysis - Samsimon, Nadia Nabila; Yusof @ Alias, Firdaus; Kamarudin, Siti Nursyahirah; Othman, Mohd Syafiq Hakimi; Abdullah, Shahirah; Hilmi, Mohd Radzi; Ahmad, Norsham; Md Mustafa, Md Muziman Syah (2020)
Aim: To analyze the prevalence of binocular vision (BV) problem and amblyopic cases in the International Islamic University Malaysia Optometry Clinic (IIUM-OC), Kuantan Pahang, Malaysia. Methodology: The present clinical-based retrospective study was conducted, and 1229 patient files from IIUM-OC presented from January 2017 to September 2018 were evaluated. All new cases files with diagnosis of BV problem and amblyopia were recorded and analyzed. Results: The prevalence of BV problem and amblyopia are respectively, 13.59% (167 patients) and 3.42% (42 patients). From the BV problem cases, the highest prevalence is accommodation insufficiency (AI) 26.3% (44 patients), followed by convergence insufficiency (CI) 23.4% (39 patients), accommodation excess (AE) 18.0% (30 patients), accommodation infacility (AF) 7.8% (13 patients), divergence excess (DE) 3.6% (6 patients), basic exophoria 3.6% (6 patients), convergence excess (CE) 3.0% (5 patients), basic esophoria 3.0% (5 patients), ill-sustained accommodation (ISA) 1.2% (2 patients), and divergence insufficiency (DI) 0.6% (1 patient); while the remaining are the combination of various BV problems at 9.6% (16 patients). For amblyopia cases, the unilateral refractive amblyopia recorded as the major type at 50.0% (21 patients). Other causes of amblyopia include strabismus with 16.7% (7 patients), and bilateral refractive with 2.4% (1 patient); while the remaining cases are the combination causes with 31.0% (13 patients). Conclusion: BV problem and amblyopia are prevalent in IIUM-OC which warrant proper management to provide a better care for the patients.